Medelacide: the intentional and systematic destruction of healthcare infrastructure - Jason C. Mueller (Global Social Challenges Journal)
When analysing recurrent global social problems, new theories and concepts often emerge. This is the outcome of not only needing a vocabulary to identify and document problems as they unfold, but to label the specific problem as one in need of solving. Once a term is developed and popularised it allows scholars, lawyers and human rights advocates to demand answers or redress from those responsible for generating such societal ills. Examples of this include the development of scholarly and legal concepts like genocide, ecocide and scholasticide. This article proposes we establish a new concept: medelacide. Medelacide describes the intentional and systematic destruction of healthcare infrastructure. After outlining a clear sociological and legal rationale for why developing this concept is necessary, I show how other concepts that address widespread human rights issues should inform our development of medelacide as an identifiable act. After providing a preliminary way to conceptualise medelacide, I offer a demonstrative case study. The case study illustrates how the act of medelacide may be identified during the first year of the Israeli government’s genocide in Gaza, Palestine. It documents how the Israeli military’s mode of assault demonstrated a pattern of intentional and systematic targeting of Gaza’s healthcare infrastructure, from October 2023 to October 2024. I conclude by offering comments on why medelacide is worth considering as a stand-alone concept, as well as one that can inform studies and analyses of structural and long-term social problems.